KURIKULUM BERBASIS CINTA DALAM PENGUATAN NILAI HUMANIS DI MADRASAH - Qori’atuz Zuhria Alwi Ramadani; M. Muizzuddin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This research is motivated by the urgent need for education that goes beyond academics to address the character, morals, and spiritual dimensions of students in facing the challenges of the times. The study focuses on the implementation of a love-based curriculum to strengthen humanist values ​​at the Mambaul Falah Blitar Qur'ani Middle School. Using a qualitative approach with a case study design, data were collected through in-depth interviews, observations, and documentation with the principal, teachers, and students. Data analysis was carried out interactively, encompassing reduction, presentation, and conclusion-drawing stages to ensure the validity of the field findings. The research results revealed that the love-based curriculum was integrated holistically through the instillation of compassion in daily interactions and academic programs. The findings indicate that the internalization of humanist values ​​such as empathy, responsibility, and social concern was successfully built through warm communication between teachers and students. Concrete steps include the use of inspirational media in learning and routine habits through religious activities. However, the main challenges lie in limited teacher competency and instructional time. The main conclusion confirms that the love-based curriculum is a strategic instrument for creating a harmonious educational ecosystem. Therefore, real efforts are needed to align humanist values ​​between the madrasa environment and the real lives of students on a daily basis in order to realize noble character qualities through strong synergy between the school, parents, and the entire community. ABSTRAK Penelitian ini dilatarbelakangi kebutuhan mendesak akan pendidikan yang melampaui batas akademik demi menyentuh dimensi karakter, moral, serta spiritualitas siswa dalam menghadapi tantangan zaman. Fokus kajian diarahkan pada implementasi kurikulum berbasis cinta guna memperkuat nilai-nilai humanis di Madrasah Tsanawiyah Qur’ani Mambaul Falah Blitar. Melalui pendekatan kualitatif dengan desain studi kasus, data dikumpulkan lewat teknik wawancara mendalam, observasi, serta dokumentasi terhadap kepala madrasah, guru, dan peserta didik. Analisis data dijalankan secara interaktif meliputi tahap reduksi, penyajian, hingga penarikan kesimpulan untuk memastikan keabsahan temuan lapangan. Hasil riset mengungkap bahwa kurikulum berbasis cinta diintegrasikan secara holistik melalui penanaman kasih sayang dalam interaksi harian maupun program akademik. Temuan menunjukkan internalisasi nilai humanis seperti empati, tanggung jawab, dan kepedulian sosial berhasil dibangun melalui komunikasi hangat antara guru dan murid. Langkah konkretnya mencakup penggunaan media inspiratif dalam pembelajaran serta pembiasaan rutin lewat kegiatan keagamaan. Meskipun demikian, tantangan utama terletak pada keterbatasan kompetensi guru dan waktu instruksional. Simpulan utama menegaskan bahwa kurikulum berbasis cinta merupakan instrumen strategis untuk menciptakan ekosistem pendidikan yang harmonis. Oleh karena itu, diperlukan upaya nyata guna menyelaraskan nilai humanis antara lingkungan madrasah dengan kehidupan nyata peserta didik sehari-hari demi mewujudkan kualitas karakter mulia melalui sinergi kuat antara pihak sekolah, orang tua, serta seluruh masyarakat.